Performance of dairy females fed dried yeast from sugar cane - Franco, Marcia de Oliveira; Marcondes, Marcos Inácio; Campos, José Maurício de Souza; Detmann, Edenio; Valadares Filho, Sebastião de Campos; Freitas, Denise Ribeiro de (Acta Scientiarum. Animal Sciences, 2016)
This study was performed in order to evaluate the effect of dried yeast from sugar cane when replacing soybean meal in dairy heifers’ diets. Twenty-four heifers, with an initial body weight (BW) of 178 kg, were distributed in a completely randomized design. The treatments were four levels of inclusion of dried yeast from sugar cane replacing to soybean meal (0, 33, 67 and 100% on a dry matter (DM) basis). While there was no difference in DM, neutral detergent fiber (NDF), metabolizable energy or roughage intakes, the intakes of non-fiber carbohydrates and concentrate were increased. The crude protein intake decreased according to the dried yeast from sugar cane when replacing soybean meal. The digestibility coefficients of DM and NDF showed no difference. Replacement of soybean meal with dried yeast from sugar cane had no effect on performance, because average daily gain and body measurements studied were similar for all animals and inclusion levels. Soybean meal can be completely replaced with dried yeast from sugar cane in diets for growing dairy heifers without restrictions; this will not affect the intake, digestibility, physical development of animals or metabolization of protein compounds.